Koreksi Akusisi Ocean Bottom Node (OBN) menggunakan First Break Positioning dan Hodogram: Studi Kasus Akuisisi Seismik 3D XRAY OBN, Offshore North West Java - Permana Citra Adi; Yayat Supriyatna (Himpunan Ahli Geofisika Indonesia (HAGI), 2022)
We present the result of applying a least square inversion approach and particle motion analysis on direct arrival wave to estimate-related error associated with ocean bottom nodes (OBN) positioning and Geophone orientation. The initial Nodes coordinates are based on acoustic positioning method at the time of deployment and before retrieval. These positions are computed on the assumption a constant water velocity which was measured directly by logging tool sound velocity profile (SVP) and therefore there are possible to have a small error in the node positions. A few nodes demonstrated excessively high shifts due to dragged by fishing net and although the node has censor to measure the Geophone orientation, some of them were not optimally re-orientated to acquisition orientation reference. Failing to correct for these errors could lead to artifacts in the velocity model, create false structures and infidelity in Geophone data. The result of these corrections on field data can improve P-Wave subsurface image quality and also correct the vector infidelity of Geophone data for S-Wave imaging, so the amplitude and kinematic information on the data is ready to be used for further analysis such as on Quantitative Interpretation (QI). Keywords: OBN, positioning, Geophone orientation, vector fidelity